Peran Pondok Pesantren Dalam Membentuk Kepribadian Santri Al Madaniyah Jaro Desa Nalui Kecamatan Jaro Kabupaten Tabalong - Akhmat Yuliansyah; Muhammad Husni (STIT Syekh Muhammad Nafis Tabalong, 2022)
The role of Islamic boarding schools in shaping the personality of students of Al Madaniyah Jaro, Nalui Village, Jaro District, Tabalong Regency. Based on this description, the formulation of the problem in this study is what is the role of Islamic boarding schools in shaping the personality of Al Madaniyah Jaro students in Nalui Village, Jaro District, Tabalong Regency and the supporting and inhibiting factors in shaping the personality of Al Madaniyah Jaro students in Nalui Village, Jaro District, Tabalong Regency. The subjects of this study were the teachers at the Jaro Al Madaniyah Islamic Boarding School, Nalui Village, Jaro District, Tabalong Regency. The techniques used in data collection are observation, interviews, and documentation. Meanwhile, to analyze the author's data using qualitative descriptive analysis. After the data has been analyzed, it can finally be concluded that the role of Islamic boarding schools in shaping the personality of Al Madaniyah Jaro students, Nalui Village, Jaro District, Tabalong Regency is the management, especially teachers, always providing teaching and education, both in worship, social, independence, nationality, discipline and obedience to rules that have been set in the boarding school environment. In terms of support, it consists of internal factors, namely teachers, family, and adequate infrastructure. While the inhibiting factors consist of internal and external. Internal factors are teachers, family and the emergence of lazy/bored instincts. While the external factor is the existence of technology that is misused by the students when they are outside the Islamic boarding school environment.